Analysis of e-commerce in Al-Qurna City (A Study in Urban Geography) - Abdul Amirki Al-Baaj, Assist. Lect . Adnan; Hashem Zegair , Prof. Dr. Salah (Basra studies journal, 2025)
This study aims to shed light on the reality of commercial use and commercial services، and the extent to which this use responds to population growth، in addition to e-shopping in the city of Qurna. The study revealed a noticeable expansion in the area of ​​commercial use as a result of the increase in the number of commercial establishments and their distribution between the central business district (C.B.D)، and the main and local streets. This highlights the direct effects on the patterns of buildings and streets. As for e-shopping، the study aimed to analyze its patterns and the impact of factors and personal characteristics of e-shoppers، and to identify the most requested needs، in addition to understanding the extent of its impact locally and regionally. This study relied on the field survey method and included a questionnaire distributed to (1312) families in (17) residential neighborhoods، in addition to (300) people from expatriates. The study concluded that the percentage of males in e-shopping increased by (54%)، with the majority of shoppers in the age group (20-30) years. The group with a monthly income of between (500-600 thousand) also recorded the highest percentage، as well as the secondary education group. The highest percentage (37%) was achieved among online shoppers.